Changes in soil labile and recalcitrant carbon pools after land-use change in a semi-arid agro-pastoral ecotone in Central Asia. (March 2020) - Liu, Xiang; Chen, Ditao; Yang, Tao; Huang, Farong; Fu, Shuai; Li, Lanhai
Highlights: The effects of land-use change on fractions and stability of SOC were investigated. LPI in topsoil and subsoil showed opposite responses to land-use change. LPII and RP stocks declined under cultivation but increased following afforestation. SOC stability decreased after cultivation and increased after afforestation. Cropland afforestation contributed to soil restoration by sequestering SOC. Abstract: Soil organic matter is a heterogeneous and complex entity that consists of a diverse range of compounds. However, the responses of soil organic carbon (SOC) fractions with different biochemical stabilities to land-use change are inadequately addressed. In this study, soil samples (0–60 cm) were collected with a 10 cm interval from grassland (GS), cropland (CS), woodland (WS), and orchard (OS) using paired-site approach in a typical semi-arid agro-pastoral ecotone in the Ili River Valley, Central Asia, to: (1) clarify the vertical changes in soil labile (LPI and LPII) and recalcitrant C pools (RP) after GS conversion to CS and CS conversion to WS and OS; and to (2) evaluate the impact of land-use change on SOC stability. The results indicated that LPI stocks in topsoil (0–30 cm) and subsoil (30–60 cm) showed opposite responses to land-use change. In contrast, LPII and RP stocks in both soil layers significantly decreased after conversion of GS to CS, and significantly increased after CS afforestation. These results demonstrated that RP in subsoils could also be altered by land-use change. In general, conversion from GS to CS decreased the recalcitrance index of SOC (RISOC ), which increased after conversion from CS to WS. The results implied that cultivation decreased the stability of SOC, causing the depletion of SOC stock, whereas CS conversion to WS enhanced the stability of SOC, promoting SOC sequestration. The negative correlations between RISOC, pH, and electrical conductivity (EC1:5 ) suggested that soil pH and salinity were potential indicators reflecting the biochemical recalcitrance of SOC. Since both soil pH and EC1:5 showed decreasing trends after conversion from CS to WS and OS, the results suggested that afforestation on CS contributed to mitigate soil salinization while promoting SOC sequestration in this semi-arid agro-pastoral ecotone.